Среди запахов и звуков: справочное издание / М. С. Плужников, С. В. Рязанцев - Плужников Мариус Стефанович (Эврика, 1991)
Экземпляры: Ф.10 (20221220) / Инвентарный номер: 49598 / Цена: 2.50 / Сис.шифр: 56.8 / Авт.знак: П 40 / ББК: 56.8 я9